Gastrointestinal Assessment and Therapeutic Intervention for the Management of Exercise-Associated Gastrointestinal Symptoms: A Case Series Translational and Professional Practice Approach - Gaskell, Stephanie K.; Rauch, Christopher E.; Costa, Ricardo J. S. (Frontiers in Physiology, 2021)
This translational research case series describes the implementation of a gastrointestinal assessment protocol during exercise (GastroAxEx) to inform individualised therapeutic intervention of endurance athletes affected by exercise-induced gastrointestinal syndrome (EIGS) and associated gastrointestinal symptoms (GIS). A four-phase approach was applied. Phase 1: Clinical assessment and exploring background history of GIS. Phase 2: Individual tailored GastroAxEx laboratory simulation. Phase 3: Individually programmed therapeutic intervention. Phase 4: Monitoring and readjustment of intervention based on outcomes from field testing under training and race conditions. Endurance athletes (n=9) presenting with EIGS completed Phase 2. Two athletes experienced significant thermoregulatory strain (peak core temperature attained >40ºC) during the GastroAxEx. Plasma cortisol increased substantially pre- to post-exercise in n=6/7 (∆ >500 nmol/L). Plasma I-FABP concentration increased substantially pre- to post-exercise in n=2/8 (∆ >1000 pg/ml). No substantial change was observed in pre- to post-exercise for systemic endotoxin and inflammatory profiles in all athletes. Breath H2 responses showed that orocecal transit time (OCTT) was delayed in n=5/9 (90-150 min post-exercise) athletes, with the remaining athletes (n=4/9) showing no H2 turning point by 180 min post-exercise. Severe Ex-GIS was experienced in n=5/9 athletes, of which n=2/9 had to dramatically reduce work output or cease exercise. Based on each athlete’s identified proposed causal factors of EIGS and Ex-GIS (i.e., n=9/9 neuroendocrine-gastrointestinal pathway), an individualised gastrointestinal therapeutic intervention was programmed and advised, adjusted from a standard EIGS prevention and management template that included established strategies with evidence of attenuating EIGS primary causal pathways, exacerbation factors, and Ex-GIS. All participants reported qualitative data on their progress, which included their previously presenting Ex-GIS, such as nausea and vomiting, either being eliminated or diminished resulting in work output improving (i.e., completing competition and/or not slowing down during training or competition as a result of Ex-GIS). These outcomes suggest Ex-GIS in endurance athletes are predominantly related to gastrointestinal functional and feeding tolerance issues, and not necessarily gastrointestinal integrity and/or systemic issues. GastroAxEx allows for informed identification of potential casual pathway(s) and exacerbation factor(s) of EIGS and Ex-GIS at an individual level, providing a valuable informed individualised therapeutic intervention approach.